2023
DOI: 10.1007/s11356-023-27796-3
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation: fresh insights to implement green supply chain management, eco-technological innovation, and collaborative capability in manufacturing sector of an emerging economy

Abstract: The increasing significance of green supply chain management in developing countries’ manufacturing sector is primarily driven by the deteriorating environment, signified by decreasing raw material resources, a surplus of waste sites, and rising pollution levels. Green supply chain management can provide competitiveness while boosting a company’s environmental sustainability if implemented effectively. Therefore, it is necessary to determine the effect of green supply chain management practices on the firm per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…According to Afum et al [40], implementing green manufacturing helped firms improve their financial performance by redesigning their production systems to comply with strict environmental laws and regulations and gain a competitive advan-tage by producing high-quality products. Furthermore, green technology innovations can improve product quality and adaptability and reduce operating costs, which tends to improve the performance of manufacturing firms [26]. According to Hu et al [41], by distinguishing between green process innovation and green product innovation, they explored how government green subsidies indirectly affect the financial performance of firms through these two types of innovations and found that by fully utilizing green process and product innovations, firms can become more competitive and sustainable, as well as improve financial performance.…”
Section: The Impact Of Green Innovation On Corporate Performancementioning
confidence: 99%
See 1 more Smart Citation
“…According to Afum et al [40], implementing green manufacturing helped firms improve their financial performance by redesigning their production systems to comply with strict environmental laws and regulations and gain a competitive advan-tage by producing high-quality products. Furthermore, green technology innovations can improve product quality and adaptability and reduce operating costs, which tends to improve the performance of manufacturing firms [26]. According to Hu et al [41], by distinguishing between green process innovation and green product innovation, they explored how government green subsidies indirectly affect the financial performance of firms through these two types of innovations and found that by fully utilizing green process and product innovations, firms can become more competitive and sustainable, as well as improve financial performance.…”
Section: The Impact Of Green Innovation On Corporate Performancementioning
confidence: 99%
“…First, a large portion of the studies is based either on cross-sectional data obtained from questionnaires [15][16][17][18][19] or using panel data but only based on the consideration of the composite construction of "green innovation" [20][21][22], resulting in inconsistent findings between green innovation and corporate financial performance [14,23]. Second, most studies focus only on the single impact of green innovation on firms' financial performance [1,24,25] or on firms' comprehensive performance indicators [26,27], and the literature lacks comparative studies on the performance consequences of different dimensions of green innovation (e.g., financial performance and environmental performance) [23]. Green innovation is a complex of corporate efficiency and legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…"Digital transformation" is influencing and shaping organizational change through digital technologies [16]. An increasing number of organizations are turning to digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics to tackle the challenges posed by a global marketplace, evolving consumer demands, emerging regulations, and talent scarcity [17]. Business executives and researchers are eagerly seeking to use the promise of these technologies, while governments are competing to incorporate them into their agendas [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Against the background of the decline in the marginal increase in the global supply of resources, the alleviation of the ecological and environmental crisis can provide a rare historical opportunity for manufacturing exports to cope with the violent external impacts of the financial crisis, COVID-19, and so on. If we can make reasonable use of the opportunities brought about by external forces, find the direction of the development of manufacturing exports, and upgrade towards digitisation, intelligence, and greening [3][4][5][6], we can not only make the manufacturing exports have a better resistance and recovery ability in the face of shocks but to even gradually adapt to the external environment and to carry out self-renewal and orientation. To realise the transformation and upgrading of the manufacturing-export growth mode towards greening, innovation and technological progress are the key factors.…”
Section: Introductionmentioning
confidence: 99%